Protein kinase inhibitor H89 enhances the activity of Pseudomonas exotoxin A-based immunotoxins - Liu, Xiufen; Müller, Fabian; Wayne, Alan S.; Pastan, Ira (Molecular Cancer Therapeutics, 2016)
HA22 (Moxetumomab pasudotox) is a recombinant immunotoxin (RIT), composed of an anti-CD22 Fv fused to a truncated portion of Pseudomonas exotoxin A. HA22 is in clinical trials to treat patients with hairy cell leukemia and acute lymphoblastic leukemia (ALL). LMB-11 is an improved variant of HA22 with reduced immunogenicity, has a longer half-life in the blood and high activity in vitro and in a Burkitt lymphoma model in vivo. Searching for RIT enhancing combination therapies, we found the protein kinase A inhibitor H89 to enhance LMB-11 and HA22 activity 5- to 10-fold on ALL cell lines and on patient-derived ALL samples. In addition, H89 increased the activity of mesothelintargeting RITs SS1P (38-fold) and RG7787 (7-fold) against the cervical cancer cell line KB31. Unexpectedly we found that the enhancement by H89 was not because of inhibition of protein kinase A; it was partially recapitulated by inhibition of S6K1, which led to inactivation of its downstream targets rpS6 and GSK3β, resulting in a fall in MCL1 levels. H89 increased the rate of ADP-ribosylation of eukaryotic elongation factor 2, enhancing the arrest of protein synthesis and the reduction of MCL1 in synergy with the RIT. In summary, H89 increased RIT activity by enhancing the two key events: ADP-ribosylation of eEF2 and reduction of MCL1 levels. Significant enhancement was seen with both CD22- and mesothelin-targeting RITs, indicating that H89 might be a potent addition to RIT treatment of CD22-positive ALL and mesothelin-expressing solid tumors.
CRIS-Team Scopus Importer:2024-12-02